Effects of Merger and Acquisition on Employee Satisfaction in Nepalese Banking Sectors - Devkota, Niranjan; Shrestha, Eliza; Mahato, Surendra; Upretee, Sahadeb; Paudel, Udaya Raj; Basyal, Devid Kumar (Journal of Business and Management, 2023)
Background: Mergers and acquisitions (M&A) are seen as effective strategies for business growth in the corporate sector. However, there are very little study on ‘merger and acquisition’ available in the context of Nepal. Objectives: This study examines the effects of mergers and acquisitions on employees’ satisfaction in Nepalese Banking sectors. Method: The study, which adopts the Job Characteristics Theory as its theoretical foundation, was conducted among employees from Nepalese banking sector that had undergone M&A. The study seeks cause and effects relationship amongst banking employees in Kathmandu valley due to merger and acquisition and adopts explanatory research design. Data were collected from 310 respondents and Structural Equation Modeling was used to analyze the data. Results: The findings demonstrate that merger and acquisition have an influence on employees’ satisfaction, with just one out of every four employees reporting high levels of satisfaction following M&A. The results exhibit that organizational climate, recognition and nature of work remain signifi cant to employees’ satisfaction and their motivation. Likewise, pay/remuneration is also statistically significant to employees’ motivation. Again, employees’ motivation also seems significant to employees’ satisfaction. Conclusion: Therefore, this study offers practical insights to human resource managers in strengthening human resources of the organization as perceived by employees after an M&A by considering the crucial role of employees in organizational performance.